Play Game Addiction on Students' Learning Attitude Public Senior High School - Petrus Kondo; Eldiani Bawone; Alfrits R. Sinadia (Pelopor Publikasi Akademika, 2023)
This study aimed to find out the correlation between playing-game addiction and students’ learning attitudes at a public senior high school, specifically to see if playing games excessively on gadgets affects students’ learning attitudes. This study used a quantitative design that was descriptive and correlative. The instruments used were adapted from two questionnaires developed by Yong (2006) and Patricia (2017). There were 120 students in grades XI and XII in natural science and Social Science at one Public High School enrolled in the second semester of the school year 2021-2022 who were the respondents to this study. The findings showed that the level of game addiction was low, with a mean score of 2.43. Furthermore, the level of students’ learning attitudes was high, with a mean score of 3.82. Next, it was found that there is a significant difference between males and females in game addiction. The mean score of Male students was 2.91 and that of female students was 2.08, which are categorized as neutral, and male students have a higher level of addiction to playing games than female students. It was found that there is a difference between male and female students in their learning attitudes, where the mean of female students was 3.96 higher than male students' 3.63, which was categorized as highly positive. Finally, it was found that there is a significant correlation between students’ game addiction and their learning attitude as p = 0.05 ? 0.05; in other words, the p-value was equal to ? = 0.05. This clearly showed that the more addicted the students are to playing games, the lower their attitude toward learning.